Laguerre-Gaussian mode division multiplexing in multimode fiber using SLMs in VCSEL arrays - Amphawan, Angela; Fazea, Yousef (Springer, 2016)
Mode division multiplexing (MDM) is a promising technology for increasing the aggregate bandwidth of multimode fiber (MMF) in conjunction with wavelength division multiplexing (WDM) in face of the impending capacity crunch in optical fiber networks.This paper investigates the effect of radial and azimuthal mode spacings in a 25-channel MDM-WDM system in MMF using a spatial light modulator-controlled VCSEL array for excitation of Laguerre-Gaussian (LG) modes.A data rate of 25Gbps is achieved at a central wavelength of 1550.12 nm.The effects of different azimuthal and radial mode spacings of LG modes are analyzed in terms of the channel impulse response, eye diagram and bit-error rate.